Trip Report for training on Rice GAPfinder: Sustainable Rice Platform (SRP): tool use for benchmarking surveys to rice farmers in framework of AICCRA project to IER partners and fields monitoring visits to check RiceAdvice Lite (RAL VAT) plots and data collected in Sikasso in Mali - Ahouanton, Kokou (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report summarizes the activities and outcomes of a training on the use of the Rice GAPfinder: Sustainable Rice Platform (SRP) benchmarking tool, conducted from August 7 to 22, 2024, under the AICCRA project in Mali. The training aimed to equip Institut d'Économie Rurale (IER) partners in Sikasso and Niono with the skills to conduct farmer interviews and use the GAPfinder SRP tool for data collection and submission. In addition, field monitoring visits were conducted across various sites in Sikasso to assess RiceAdvice Lite (RAL VAT) plots and ensure data accuracy. The training prepared participants to survey 450 rice farmers and supported the validation of rice cultivation practices, contributing to data-driven agricultural advancements.